Laser-Induced Electron Diffraction for Probing Rare Gas Atoms - Xu, Junliang; Blaga, Cosmin I.; DiChiara, Anthony D.; Sistrunk, Emily; Zhang, Kaikai; Chen, Zhangjin; Le, Anh-Thu; Morishita, Toru; Lin, C. D.; Agostini, Pierre; DiMauro, Louis F. (My University, 2012)
Recently, using midinfrared laser-induced electron diffraction (LIED), snapshots of a vibrating diatomic molecule on a femtosecond time scale have been captured [C. I. Blaga et al., Nature (London) 483, 194 (2012)]. In this Letter, a comprehensive treatment for the atomic LIED response is reported, a critical step in generalizing this imaging method. Electron-ion differential cross sections (DCSs) of rare gas atoms are extracted from measured angular-resolved, high-energy electron momentum distributions generated by intense midinfrared lasers. Following strong-field ionization, the high-energy electrons result from elastic rescattering of a field-driven wave packet with the parent ion. For recollision energies ≥100 eV, the measured DCSs are indistinguishable for the neutral atoms and ions, illustrating the close collision nature of this interaction. The extracted DCSs are found to be independent of laser parameters, in agreement with theory. This study establishes the key ingredients for applying LIED to femtosecond molecular imaging.